Effect of wheat bran on gluten network formation as studied through dough development, dough rheology and bread microstructure - Gajula, Hyma (Kansas State University, 2017)
The overall hypothesis underlying this study is that the nature and extent of bran interactions with the gluten protein matrix play a dominant role in both 'in-process' dough and final product quality of whole grain baked goods. Therefore, the purposeful manipulation of those interactions should be able to minimize adverse processing or product characteristics resulting from bran inclusion/presence. The approach we took was to study the effects of bran milled to different particle sizes on dough development during and after dough mixing using fundamental rheology combined with traditional cereal chemistry approaches and x-ray microtomography (XMT). The research outcomes were used to create a better picture of how the bran is effecting the dough development and to suggest strategies that allow for the control of that effect. Study-I focused on characterization of the chemical properties, empirical rheological properties and baking performance of flours and dough with different bran contents from different sources. The development of dough microstructure and the resulting crumb texture in the presence of different bran were studied using XMT. HRW and SW bran additions resulted in higher water absorptions (WA) irrespective of the flour type and bran source. Fine bran caused slightly higher WA followed by coarse and as is bran. Both HRW and SW bran decreased the dough stability of HRW flour, while it improved the stability of SW flour doughs. Macro and microstructure of baked products were significantly affected both bran type and addition level. HRW bran added to HRW flour resulted in 8-23% decrease in loaf volume while SW bran added at the same level caused 3-11% decrease. XMT indicated that bran decreased the total number of air cells significantly. SW flour resulted in harder crumb texture than that of HRW flour breads. Overall, SW bran had less detrimental effects on mixing and baking performance of HRW flour. Study-II focused on specific bran particle size and composition on small and large deformation behavior of strong and weak flour doughs. Small deformation behavior was characterized using frequency and temperature sweep tests, while the large deformation behavior was studied using creep–recovery and uniaxial extensional testing. The results revealed that the rheological behavior of bran-enriched doughs depend on type of base flour, bran type, bran replacement level (0, 5, 10%), and the dough development protocol. Weak flour doughs benefited from inclusion of bran as inherently low peak height and stability of these doughs improved in the presence of bran. Temperature sweeps indicated a slight decrease in Gʹ and G" until around 55-60°C. In the same temperature range, presence of bran increased the moduli of composite four compared to that of the control flours. Creep compliance parameters indicated that both bran source and bran replacement had significant effect on maximum compliance (J[subscript max]) and elastic compliance (J[subscript e]). Finally, the bran type affected uniaxial extensional properties, maximum resistance (R[subscript max]) and elasticity (E), significantly independent from the type of base flour.
Keywords: Wheat flour; Bran; Dough development; Dough rheology; Microstructure; Texture